Exploring temporal and functional synchronization in integrating models: A sensitivity analysis. (May 2016) - Belete, Getachew F.; Voinov, Alexey
Abstract: When integrating independently built models, we may encounter components that describe the same processes or groups of processes using different assumptions and formalizations. The time stepping in component models can also be very different depending upon the temporal resolution chosen. Even if this time stepping is handled outside of the components (as assumed by good practice of component building) the use of inappropriate temporal synchronization can produce either major run-time redundancy or loss of model accuracy. While components may need to be run asynchronously, finding the right times for them to communicate and exchange information becomes a challenge. We are illustrating this by experimenting with a couple of simple component models connected by means of Web services to explore how the timing of their input–output data exchange affects the performance of the overall integrated model. We have also considered how to best communicate information between components that use a different formalism for the same processes. Currently there are no generic recommendations for component synchronization but including sensitivity analysis for temporal and functional synchronization should be recommended as an essential part of integrated modeling. Highlights: We coupled predator and prey models using Web services. Integration of models is highly sensitive to the time steps assigned to each models. Integration output is sensitive to numeric integration methods used by components. Integration output is sensitive to functional responses used by participating models.